Analysis of Slope Stability in Embankment Areas 'Shaiful Dump' at PT Agincourt Resources, North Sumatra - Okky Chandra Perdana; Barlian Dwinagara; S Koesnaryo; Saptono Singgih (Science and Environmental Journal for Postgraduate, 2023)
The safety factor from the stability of a slope is one of the important things that must be considered, especially in open pit mine planning such as the system implemented by PT Agincourt Resource. Research on the "Syaiful Dump" dumping area aims to find the value Safety Factor (FK) on the embankment slopes, as well as evaluate the initial design plan that has been determined by the company at an Overall Slope angle of 12°. The research was carried out by making a redesign based on an evaluation of the initial slope design with an overall slope of 12°. Slope redesign made with overall slope values of 15°, 20°, 25° and 30°. Variation of slope angle aims to get a value FK which is close to or above a predetermined standard, namely FK> 1.3. The assumptions used in the modeling, namely the groundwater level is 3 MBGL, the seismic factor is 0.25 g, and the arc avalanche trajectory is assumed to cross colluvium material (low strength material). Using the Morgenstern – Price calculation method, the FK value for a slope angle of 12° is 1.7; 15° by 1.6; 20° by 1.4; 25° by 1.2; and for a slope angle of 30° the FK value is 1.0. From the calculation results, it can be recommended for an overall slope angle of 20° with a value of FK = 1.4. This value is by the standards set.